Serum Zinc, Copper and Calcium Levels In Female Rheumatoid Arthritic Patients - Jelly, Arifa Alam; Begum, Shelina; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2012)
Background: Rheumatoid Arthritis is a chronic multi-system autoimmune inflammatory disease, characterized by inflammatory synovitis involving symmetrical peripheral joints. Serum copper, zinc and calcium levels are altered in Rheumatoid Arthritis. Objective: To observe serum zinc, copper and calcium levels in patients with Rheumatoid Arthritis (RA). Methods: This cross sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from January to December 2010. For this, 60 female patients with Rheumatoid arthritis aged 30-50 years were included in the study group. The patients were selected from outpatient Department of Rheumatology wing of medicine in Bangabandhu Sheik Mujib Medical University (BSMMU). For comparison age and BMI matched 30 apparently healthy female were also studied. Serum calcium level was measured by Colorimetric method. Serum zinc and copper was measured by Spectrophotometric method. For statistical analysis, independent sample t test was performed by using SPSS for windows version-12. Results: In this study, serum zinc and calcium levels were significantly lower (p<0.001) and serum copper level was significantly higher (p<0.001) in the RA patients than those of control. Conclusion: This study may conclude that hypozincemia and hypocalcemia and hypercupremia occur in RA. Therefore early detection of these micronutrient abnormalities may be helpful for the physicians to prevent various complications in RA patients. DOI: http://dx.doi.org/10.3329/jbsp.v7i1.11155 J Bangladesh Soc Physiol. 2012, June; 7(1): 18-22